2019
DOI: 10.1002/rev3.3165
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of computer‐assisted pronunciation training: A meta‐analysis

Abstract: Computers are used in almost all aspects of language learning and have also created numerous opportunities in this area. This study aims to examine the overall effectiveness of using a computer in pronunciation learning and training. A meta‐analysis of studies was conducted, which compared the outcomes of students learning the pronunciation of a foreign language (FL) using a computer with the results from those learning pronunciation based on traditional methods of teaching. This meta‐analysis examined how eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 47 publications
4
27
0
Order By: Relevance
“…Chun et al [28] claimed that the use of technology should neither be seen as a panacea, nor as a goal in and of itself, but rather as but one means to support specific learning goals. The results are in line with the Mahdi and Al Khateeb, [29] research result that the use of Computer Assisted Pronunciation Technology (CAPT) is more beneficial for university students, and that it could be more effective when pronunciation is presented inside rather than outside the classroom. Unlike the other language skills, pronunciation learning is a complex task; students struggle to learn by themselves, which can lead them to feel dependent on an instructor for regular feedback.…”
Section: Resultssupporting
confidence: 86%
“…Chun et al [28] claimed that the use of technology should neither be seen as a panacea, nor as a goal in and of itself, but rather as but one means to support specific learning goals. The results are in line with the Mahdi and Al Khateeb, [29] research result that the use of Computer Assisted Pronunciation Technology (CAPT) is more beneficial for university students, and that it could be more effective when pronunciation is presented inside rather than outside the classroom. Unlike the other language skills, pronunciation learning is a complex task; students struggle to learn by themselves, which can lead them to feel dependent on an instructor for regular feedback.…”
Section: Resultssupporting
confidence: 86%
“…The findings on the third research question indicated active behavioral engagement of the participants in extending their time to write and revise. Such a dynamic self-regulated learning behavior has been supported as the action-based impact of DIA by several researchers (Carless & Boud, 2018 ; Doe, 2015 ; Mahdi & Al Khateeb, 2019 ). Regarding the emotional engagement of participants in DIA, the students experienced a low-stress environment, community membership, and simplicity in computer-assisted DIA on Google Meet.…”
Section: Discussionmentioning
confidence: 86%
“…They are also fun, motivating, and cost‐effective (e.g., Lyytinen et al, 2007; Ronimus, Kujala, Tolvanen, & Lyytinen, 2014). Extensive research has demonstrated that as a supplementary learning tool, computer‐assisted training facilitates many aspects of literacy development such as phonological awareness (e.g., Chai, Ayres, & Vail, 2016), decoding (see Mahdi & Khateeb, 2019 for a meta‐analysis), and vocabulary (see Chen, Tseng, & Hsiao, 2018 for a meta‐analysis). According to Chen et al (2018), the design of a game influences learning outcomes, regardless of a learner's age or linguistic background.…”
Section: Using the Self‐adaptive Graphogame To Enhance Pinyin Learningmentioning
confidence: 99%